Experimental and Numerical Studies on Bond Quality of Fully Grouted Rockbolt under Confining Pressure and Pull-Out Load - Shuisheng Yu; Leilei Niu; Jin Chen (Shock and Vibration)
In mining engineering, the in situ stress changes with the stress induced by the surrounding mining activities. It positively or negatively affects the propagation of ultrasonic guided waves in rockbolts. Therefore, the effect of in situ stress in rockbolt support was determined by applying confining pressure and pull-out load in a laboratory test and using ultrasonic guided waves to test the rockbolt. Furthermore, the propagation law of ultrasonic guided waves and bond quality of the rockbolt under the interaction of the pull-out load and confining pressure were studied. Numerical simulations were performed to deduce the guided wave propagation process in grouted systems, and the influencing mechanism of the pull-out load and confining pressure on the guided wave propagation was discussed. The laboratory test and numerical simulation results show that the confining pressure weakens the guided wave propagation without pull-out load. Under the same pull-out load, the guided wave propagation gradually strengthens with increasing confining pressure. A larger confining pressure weakens the weakening effect of the pull-out load and suppresses the discreteness of the guided wave propagation. Under the same confining pressure, the guided waves did not diffract well into the cement mortar and concrete with increasing pull-out load, the confining pressure restricted the radial vibration of the guided waves, and the guided wave propagation law weakened. Thus, the pull-out load plays a weakening role in the propagation law of ultrasonic guided waves.